Antinomy of Investment Law: Problems of Ideology, Framework and Regulatory Conflict - Purwanto Purwanto; Markus Yohanis Hage (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The development of investment in Indonesia began in the 1960s with the enactment of Law No. 1 of 1967 concerning Foreign Investment and Law No. 6 of 1968 concerning Domestic Investment. This research is classified as doctrinal research, namely research that understands law as the principles of truth and justice that are natural and universally applicable. The data sources for this research consist of primary and secondary data. The analysis techniques in this research include normative and ideological interpretations of laws and constitutional documents. This analysis aims to uncover the meaning of the values contained in investment legal norms and their relationship to the ideology they carry. The ideology that accompanies investment, namely the elite social construction that does not provide opportunities for people's economic empowerment towards independence and productivity. The idea of designing 'what' will be achieved through investment, 'how' the idea is expressed in the form of legal institutions/institutions, and 'to what extent' the process of understanding and deepening of these institutions and institutions, is a dialectical circle of struggle between the economic elite and the power elite. The source of the idea is capitalist liberal ideology, the locus of market thinking that makes profit a never-ending and never-culminating pursuit.